PENGGUNAAN ALAT METRONOM DINGKLIK (METRODINK) PADA LATIHAN FISIK SENAM DINGKLIK MENURUNKAN BERAT BADAN DAN MENINGKATKAN KEBUGARAN FISIKPADA KEGEMUKAN - I Wayan Juniarsana; Ni Komang Wiardani (JURNAL SANGKAREANG MATARAM, 2017)
Background. The prevalence of obesity increased sharply every year due to less of physical activities and food consumption pattern tends to high energy and highfat. The prevalence of overweight and obesity for adult above of 18 years old about 11,7% (Riskesdas, 2010). The study aims to know the effect of metronomedingklikaerobic with low energy diet towards for decreasing of body weight and increasing of physical fitness for obesity women. Methods: The study was experimental design with randomized pre test-post test control group design. Subject was women whose a member of PKK in Denpasar city with criteria age was 30–45 years old, body mass index are 25–29,9. The subject was divided into three groups with randomized e.q Group I was given metronome dingklik gymnastics including low energy diet, Group II was given dingklikgymnastics without metronome including low energy diet and Group III was given only low energy diet.Results: According to bivariat analysis shown that body weight significantly and physical fitness increase significantly by metronome dingklik gymnastics with low energy diet intervention (group I) but there was no significant bydingklikgymnastics without metronome with low energy diet (group II) and only low energy diet treatment (group III). Analysis by one way anova (within group) shows that all of treatment. But according to two group intervention shows that metronomedingklikgymnastics with low energy diet was the most effectively way for decreasing weight and increasing physical fitness for obesity women.